The development of an artificial intelligence system for robot soccer - Carreon, Mario; Gonzalez, Orland; Niguidula, Anna Carmela; Ongkingco, Neil; Tubadeza, Jose Carlo (2001)
The goal of this research is to develop an artificial intelligence system that will control the multiple robots in the robot soccer field to act in a manner that will win them the game. This involves the determination and implementation of the basic motion control, robot behaviors, roles and strategies. For the motion control, the limit cycle, proportional derivative and proportional cosine method were used. The ball coordinates were predicted using a weight function on the ball history. Simple intermediate point generation were used for obstacle avoidance and wall escape. Aggresive and defensive robot behavior were also implemented Scripted plays, position-based role switching and strategic role assignments (1-1-1, 1-2-0 and 1-0-2) were developed. Games have shown that speed and aggresiveness are more important than accuracy. It was also found that prediction and overrides take advantage of the dynamic nature of robot soccer. The limit cycle and proportional derivative proved to be excellent tools in movement control.